EDUCATIONAL SYSTEM OF THE REPUBLIC OF UZBEKISTAN. REFORMS OF EDUCATION. TYPES OF EDUCATIONAL INSTITUTIONS. ECONOMIC DEVELOPMENT. DEVELOPMENT STRATEGIES OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi; Mo’minova Odina G’ulom qizi (TADQIQOTLAR.UZ, 2024)
Annotation: The educational system of the Republic of Uzbekistan has undergone significant reforms in recent years aimed at modernizing and enhancing the quality of education. This article provides an overview of the reforms implemented in the Uzbekistan education system, focusing on key changes and initiatives. It discusses the types of educational institutions present in Uzbekistan and their roles in the education system. Through an examination of government policies, educational structures, and emerging trends, this article sheds light on the current state of education in Uzbekistan and its trajectory for the future. Keywords: Uzbekistan, education reform, educational institutions, government policies.